1997
DOI: 10.1210/jcem.82.8.4149
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density, Body Composition, and Lipid Metabolism during Growth Hormone (GH) Treatment in Children with GH Deficiency1

Abstract: Adults with childhood onset GH deficiency (GHD) have reduced bone mass, increased fat mass, and disorders of lipid metabolism. The aim of the present study was to evaluate bone mineral density (BMD), bone metabolism, body composition, and lipid metabolism in GHD children before and during 2-3 yr of GH treatment (GHRx). Forty children with GHD, mean age 7.9 yr, participated in the study of bone metabolism and body composition; and an additional group of 17 GHD children, in the study of lipid metabolism. Lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(11 citation statements)
references
References 49 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Also in 1997, Boot and colleagues in their prospective study analyzed 40 children with GHD and found an increase of the 1,25(OH) 2 D levels during the substitution treatment with rGH, without variations in PTH and the calcium levels. At baseline, the values of 1,25(OH) 2 D were in the normal range, which excluded the presence of a basal hypovitaminosis D. The 25(OH)D values are not known because they were not considered in this study [80].…”
Section: Vitamin D Metabolism and Gh In Clinical Pediatric Studiesmentioning
confidence: 99%
“…Also in 1997, Boot and colleagues in their prospective study analyzed 40 children with GHD and found an increase of the 1,25(OH) 2 D levels during the substitution treatment with rGH, without variations in PTH and the calcium levels. At baseline, the values of 1,25(OH) 2 D were in the normal range, which excluded the presence of a basal hypovitaminosis D. The 25(OH)D values are not known because they were not considered in this study [80].…”
Section: Vitamin D Metabolism and Gh In Clinical Pediatric Studiesmentioning
confidence: 99%
“…The bone growth and development are profoundly affected by the growth hormone (GH) and other factors such as insulin-like growth factor (IGF). It has been shown that hyposecretion of GHs causes a decrease in bone mineral density (BMD), while GH facilitates bone growth and strength . IGF is essential for bone growth and maturation .…”
Section: Discussionmentioning
confidence: 99%
“…GH treatment increases plasma phosphate concentrations in GHD children [73,74] and adults [52,53,75]. In contrast to plasma calcium concentrations, this increase in plasma phosphate persisted during 12-24 months of GH therapy [53,[73][74][75], while urinary phosphate excretion was decreased. .…”
Section: Ghd and Kidneymentioning
confidence: 94%
“…It is well known that adult GHD patients present osteoporosis with a high risk of vertebral and femoral fractures. Low bone mass can be partially improved by GH replacement [70][71][72][73] because GH therapy in GHD adults causes a transient increase in plasma calcium concentrations and urinary calcium excretion, which usually lasts between 3 and 6 months.…”
Section: Ghd and Kidneymentioning
confidence: 99%